Perancangan Konveyor Pembersih Kotoran Ayam Broiler Bertingkat Otomatis dengan Metode Perancangan VDI2222 - Bustami Ibrahim; Sidik Permana; Fathurrizqi Raffiq (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2025)
This research was conducted based on a request from PT Paranje Rizqi Cileuncang to Politeknik Manufaktur Bandung to design a broiler chicken manure cleaning system. The system was designed according to the chicken coop construction built by PT Paranje Rizqi Cileuncang in Kabupaten Garut, measuring 17 meters in length, 5 meters in width, and 7 meters in height, with 5 levels and 2 columns of cages. The research aimed to design and determine the cost of manufacturing the broiler chicken manure cleaning system. The design process followed the VDI 2222 methodology, which includes planning, conceptualizing, designing, and finalizing. The results of this study include a draft, 3D modeling, working drawings, and a detailed cost estimation. The designed system is a belt conveyor placed under the chicken coop, equipped with a drive motor, rollers, pulleys, and a belt cleaner. The estimated cost of the conveyor system is IDR.181,463,156